Upploppet som det absoluta konstverket - Björk, Johannes; Wikström, Josefine (K&K - Kultur og Klasse, 2023)
In this article, we suggest that the notion of “aesthetic cultures of protest” can be understood as designating two broad tendencies in the contemporary field of art and politics: on the one hand, the incorporation of the protest by the art world and, on the other hand, the appropriation of aesthetic traits by social protests. To counteract the ethical immediacy of both, we turn to Theodor W. Adorno’s more dialectical understanding of the relationship between protests and the aesthetic. After being marshalled against art’s internalisation of protest, and the protests’ appropriation of the aesthetic, we assess Adorno’s notion of form and autonomy through an immanent critique that is both conceptual and historical. We argue that Adorno’s aesthetics lacks an understanding of social labour, to which it itself ascribes great conceptual significance, and that recent changes in the global composition of capital and labour has affected the role of social labour in such a way that Adorno’s tendency to identify art’s autonomy with its negativity can no longer be upheld. Finally, we argue that the characteristics, which Adorno ascribes to the work of art has migrated to, and been realised by, a form of protest which reemerged simultaneously with the death of Adorno, namely the riot.